IMPLEMENTASI PELAPORAN DIGITAL KAMPUNG KB PADA KAMPUNG KB GAYUB KOTA SURABAYA - Trisnawati, Ananda Eka Putri; Nafi’ah, Binti Azizatun (Jurnal Progress Administrasi Publik, 2024)
This research aims to find out how the KB Village Website is implemented, in KB Gayub Village, Gunung Anyar Village, Gunung Anyar District, Surabaya City. The method used is a qualitative descriptive approach. The data sources obtained are primary and secondary data types, where data collection techniques are carried out through observation, interviews, and literature studies from several articles, journals, and news that are relevant to the discussion in this research. The research uses Sujianto's theory of policy implementation which was chosen as analysis material to see the findings in the field. The results of the research show that the implementation of Digital Reporting for KB Village via the Gayub KB Village Website in Gunung Anyar Village, Gunung Anyar District, Surabaya City is not yet optimal, based on a theoretical study of policy implementation by Sujianto which consists of four indicators, namely communication, resources, disposition and policy benefits. Of these four indicators, what is still an obstacle is the lack of communication and the lack of competence possessed by human resources in the ability to input and report activities on the KB Gayub Village Website, Gunung Anyar District.    Keywords: Implementation; Reporting; Digital; Village